Perancangan Sistem Informasi Akuntasi Penentuan Harga Pokok Produksi Dengan Metode Full Costing Berbasis Desktop Di PT. Kentang Hollando Sejahtera - Faizar Kurniawan; Resmi Ranti Rosalina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research objective is to design an accounting information system for determining the cost of production at PT. Hollando Sejahtera potatoes and to be implemented according to the company's needs. The design of the accounting information system uses the full costing method and the method of gathering information and supporting data during this research using observation, interviews and literature studies. Software for information system development uses Microsoft Visual Basic and for databases uses MySQL. System development in this study uses the Waterfall method. The documents used are the use of materials, labor, and overhead during the production process. The data processing stage is presented in data tables and their relations in the form of an ERD. The data processing stage is presented in a flowchart and program interface design. The input design consists of raw material transactions, supporting material transactions, labor cost transactions, overhead cost transactions, harvest data. The output designs are inventory reports, HPP reports, general journal reports and harvest reports. The result of this research is to replace an existing system which is still simple and inaccurate in determining production HPP, and the results of implementing this system are able to assist in recording, controlling and reporting from the production team to company management making it easier for company management to make decisions and policies for the next production process. Keywords: Accounting Information System, HPP, Full Costing